2003
DOI: 10.1002/pen.10019
|View full text |Cite
|
Sign up to set email alerts
|

Essential work of fracture of polypropylene and polypropylene blends over a wide range of test speeds

Abstract: The mechanical properties of extruded films of isotactic polypropylene (iPP) and ethylene‐propylene rubber toughened iPP (iPP/EPR) have been analyzed in terms of the specific essential and non‐essential work of fracture using high speed tensile test apparatus modified for quasi‐static testing in the range 0.0001 to 3 ms−1. Three iPP/EPR grades with modifier contents of 15, 21 and 30 vol% were investigated. As the deformation rate increased, relatively uniform necking of the whole ligament and extensive plastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 29 publications
4
31
0
3
Order By: Relevance
“…PWFs reported for PETG from these same studies include 7.7, 16 7.5, 10 and 8. 5 This EWF is close to that found in the present study, but the PWF is less than half that reported here. It should be noted that the vol.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…PWFs reported for PETG from these same studies include 7.7, 16 7.5, 10 and 8. 5 This EWF is close to that found in the present study, but the PWF is less than half that reported here. It should be noted that the vol.…”
Section: Resultssupporting
confidence: 91%
“…% EPR in the materials evaluated in the present study is unknown. At loading rates similar to those used in this study, Grein et al 5 found that both EWF and PWF decrease as rubber content increases.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…2). Any molecular process that promotes energy dissipation enhances the impact resistance of the polymer, as indicated by Kausch's statement [37]. The data obtained from the different techniques reveal that the incorporation of small amounts of PPS-NH2-g-SWCNTs favours the energy dissipation, hence improves the impact resistance of the matrix.…”
Section: Mechanical Propertiesmentioning
confidence: 91%
“…Previous works showed that double plastic zone phenomenon was not visible for all materials and it was only reported in studies on the fracture behaviors of block copolypropylene 25,26 and blend of iPP/EPR. 27 The value of b can be determined by the ratio of h (height of plastic zone) to l, as recommended in the first EWF protocol version. 10 It is worth noting that the value of b should be determined by the height of DOPZ or IOPZ.…”
Section: Plastic Deformationmentioning
confidence: 99%